ECONOMIC TERMINOLOGY – NEW PERSPECTIVES - Museanu, Elena (European Scientific Journal, ESJ, 2013)
The analysis starts from the premise of the differential partial behavior of terms in various types of economic discourse – scientific and environment related (in the economic press of wide circulation). Examples considered concern the preservation of the hard core of the specialized meaning and the conceptual-semantic effects triggered by contextual combinations in different types of texts. The terminological variation in the current economic texts is primarily conditioned by the evolution of companies, and the economic press of wide circulation is forced to reflect the dynamics of changes, which happen before our eyes, and are not yet reflected in the strictly scientific texts since they develop slower. The strict extra-linguistic determination entails a more rigorous use of the economic terms, with definitions and inter-conceptual relations manifested at the level of the terminological density, which are rather high in texts of wider circulation.